2008
DOI: 10.1017/s1751731108002735
|View full text |Cite
|
Sign up to set email alerts
|

Using the alkanes and long-chain alcohols of plant cuticular wax to estimate diet composition and the intakes of mixed forages in sheep consuming a known amount of alkane-labelled supplement

Abstract: In a feeding trial with 24 sheep, we used the alkanes, long-chain alcohols (LCOH) or both of these plant wax markers, to estimate the diet composition of animals offered diets comprising alkane-labelled cottonseed meal (CSM) together with up to four forages. The diets used were: Diet 1 subterranean clover (Trifolium subterraneum); Diet 2 subterranean clover 1 phalaris (Phalaris aquatica); Diet 3 subterranean clover, phalaris 1 annual ryegrass (Lolium rigidum); and Diet 4 subterranean clover, phalaris, annual r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

26
52
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(79 citation statements)
references
References 18 publications
26
52
1
Order By: Relevance
“…Marker profiles of the plant species Results on LCOH profiles of the plant species used in this study are consistent with results of previous reports (Dove and Charmley, 2008;Lin et al, 2009;Ferreira et al, 2015) that reported a trend for higher total LCOH concentrations than those of alkanes for the majority of plant species, especially in herbaceous species. In general, herbaceous species are known to possess very low total alkane concentrations (Dove and Mayes, 2006;Oliván et al, 2007b).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Marker profiles of the plant species Results on LCOH profiles of the plant species used in this study are consistent with results of previous reports (Dove and Charmley, 2008;Lin et al, 2009;Ferreira et al, 2015) that reported a trend for higher total LCOH concentrations than those of alkanes for the majority of plant species, especially in herbaceous species. In general, herbaceous species are known to possess very low total alkane concentrations (Dove and Mayes, 2006;Oliván et al, 2007b).…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were also observed in previous studies performed with sheep for the same markers (Dove and Charmley, 2008;Lin et al, 2009;Ferreira et al, 2015), and goats (Ferreira et al, 2012). In previous studies conducted with horses and cattle, an incomplete FR of alkanes (Ferreira et al, 2007) and LCFA (Ferreira et al, 2010) was observed.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations